Hubungan Kelebihan Berat Badan Karyawan Dengan Peningkatan Kadar Kolesterol Di Balai Kesehatan Kebun Jatirono Kecamatan Kalibaru - Ratih Eka Fitrianingrum; Ferry Diana Karmilasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research reviews the relationship between body weight and increased cholesterol levels. This research was carried out at the Kebun Jatirono Health Center, Kalibaru District, Banyuwangi using observational analytical research and using cross-sectional measurements because in this research the researcher aims to determine the existence of a relationship between the two variables being studied by only observing without intervention on the variables to be studied and measurements or observations of respondents who were overweight were 22 employees or 73.3%. Then, most of the employees at the Kebun Jatirono Health Center, Kalibaru Banyuwangi District who were respondents experienced increased cholesterol levels, namely 14 people or 46.7% had moderate cholesterol levels. And there is a relationship between employee overweight and increased cholesterol levels at the Kebun Jatirono Health Center, Kalibaru Banyuwangi District. Using the Spearman Rank Correlation statistical test, the calculated ρ value = 0.573 > from the table ρ value = 5% Error Degree = 0.363 and 1% Error Degree = 0.478.